Cissus quadrangularis: Anthelminthic Activity and Biological Consumption Substantiation - CHIFAMBA, JOEY; SAI, SIFISO R; MUTAMBANENGWE, WADZANAI S; CHAGONDA, FORTUNE (Journal of Complementary and Alternative Medical Research, 2025)
Cissus quadrangularis from the Vitaceae family is a widespread perennial climber prevalent in tropical and subtropical regions of Africa. In Zimbabwe, the square stemmed (quad) plant is mostly found in open woodlots mostly climbing mopane trees. This plant has been extensively used in traditional medicine for various conditions but mostly as an anti-helminthic, hence the local name muvengahonye. The aim of this study was to confirm the metabolomic profile of pharmacological relevance, the acute oral toxicity profile, the anti-helminthic as well as the antibacterial activity of the plant. Phytochemical analysis was done using classical wet chemical tests. The OECD guideline 425 was used to evaluate the acute oral toxicity using Sprague Dawley rat models. The antibacterial activity was confirmed using the macrodilution broth test following CLSI guidelines with doxycycline as the control and the anthelminthic evaluation was conducted against Pheretima Posthuma earthworms with 20mg Albendazole as a standard. The metabolomics revealed the presence of significant pharmacologically active secondary metabolites including polyphenols, flavonoids and alkaloids. The lyophilised extract demonstrated antibacterial activity comparable to doxycycline against gram positive Staphylococcus Aureus as well as gram negative Escherichia coli. The acute oral toxicity study confirmed that C. quadrangularis is nontoxic with an LD50 above 2000mg/kg.  The anthelmintic activity demonstrated that the plant was effective in rendering both paralysis and death to the Indian earthworm (Pheretima Posthuma) with time frames comparable to albendazole. Our findings validate the use of the plant in traditional medicine as an effective and biologically safe anthelminthic treatment.